HUBUNGAN INDEKS MASSA TUBUH DENGAN BODY IMAGE PADA SISWI SMK SENTRA MEDIKA TAHUN 2018 - Saiful Batubara; Wahyu Ardiansyah Batubara (Jurnal Kajian Kesehatan Masyarakat, 2019)
Background: In adolescence, there is an increase in muscle mass and fat tissue. This change is related to nutritional status that can be assessed by measurement of Body Mass Index (BMI). At the age of adolescents, it begins to recognize the body shape or body image, the biggest problem that many adolescents are not satisfied with their body shape. Research method: This research type is observational analytic research with cross sectional approach, which was done on December 2017. The population of this research included students of class XII SMK Sentra Medika Medan, with number is 56 people. Sampling with total sampling technique, as many as 56 taken. Data obtained from measurement of IMT and questioner on respondent, then data were analyzed univarite and bivariate with computer using Chi Square Statistical Test. Results: The results showed that who had a thin IMT of 28.6%, normal BMI 37.5% and BMI weight 33.9% more. Students have a dissatisfied body image 44.6% while female students have a satisfied body image of 55.4%. The results of statistical tests show (P = 0.004) means there is a Body Mass Index Relation with Body Image on SMK Sentra Medika Medan students in 2018.Conclusion: From the research result it can be concluded that there is a significant relationship between Body Mass Index (BMI) and Body Image on SMK Sentra Medika Medika Students Year 2018.